ANALYSIS OF THE IMPLEMENTATION OF THE MINING SAFETY MANAGEMENT SYSTEM BASED ON THE DECISION OF THE DIRECTOR GENERAL OF MINERALS AND COAL NUMBER 185.K/DJB/2019 AT PT X SITE MURUNG RAYA - Prana; Maulana Yusuf; M. Taufik Toha (RADJA PUBLIKA, 2026)
This study aims to understand the extent to which the Mining Safety Management System (SMKP) is implemented, identify differences in its implementation, and analyze factors that influence the effectiveness of the system. The study was conducted at PT X Site in Murung Raya Regency, Central Kalimantan Province. The research method used a descriptive approach that combines quantitative and qualitative. The study population included all employees and company management, and sampling was carried out using the stratified random sampling method. Data collection techniques were carried out by conducting interviews, direct observations in the field, and studying various documents owned by the company. Data analysis was carried out by calculating the percentage of achievement, explaining the actual situation, and comparing it with the standards contained in the Decree of the Director General of Minerals and Coal Number 185.K / DJB / 2019. This study shows that in general the level of SMKP implementation at PT X Site Murung Raya reached 64.20%. The results of this level of achievement indicate that the main problems are in field implementation, personnel availability and competence, and follow-up mechanisms and continuous improvement. Meanwhile, elements of policy, planning, and documentation have been running well. Based on these results, it can be concluded that the SMKP has been implemented with a strong foundation, but it has not yet been implemented effectively. Increased supervision, increased manpower, and system improvements and follow-up are needed to optimally achieve the goals of occupational safety and health protection